Post-vehicle-application lithium-ion battery remanufacturing, repurposing and recycling capacity: Modeling and analysis - Charles R. Standridge; Md Mehedi Hasan (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: A mathematical model is used to help determine the manufacturing capacity needed to support post-vehicle-application remanufacturing, repurposing, and recycling of lithium-ion batteries over time. Simulation is used in solving the model to estimate capacity in kWh. Lithium-ion batteries that are commonly used in the electrification of vehicles cannot be simply discarded post-vehicle-application due to the materials of which they are composed. Eventually, each will fail to hold a charge and will need to be recycled. Remanufacturing, allowing a battery to return to a vehicle application, and repurposing, transforming a battery for use in a non-vehicle application, postpone recycling and increase value. The mathematical model and its solution using simulation test the hypothesis that the capacity needed for remanufacturing, repurposing, and recycling as well as new battery production is a function of a single parameter: the percent of post-vehicle-application batteries that are remanufactured. Design/methodology/approach: Equations in the mathematical model represent the capacity needed for remanufacturing, repurposing, and recycling as well as new battery production as dependent variables. Independent variables are exogenous quantities as such as the demand for electrified vehicles of all types, physical properties of batteries such as their application life distribution including the time to recycling, and a single decision variable: the percent of post-vehicle-application batteries that are remanufactured. Values of the dependent variables over time are estimated by simulation for values of the percent of post-vehicle-application batteries ranging from 0% to 85% in steps of 5%. Findings and Originality/value: The simulation results support important insights for investment in capacity for remanufacturing, repurposing, and recycling of post-vehicle-application batteries as well as new batteries. The capacity needed for recycling is relatively constant regardless of the percent of post-vehicle-application batteries that are remanufactured. The sum of the capacity for remanufacturing and recycling is relatively constant as well. The need for new battery production capacity is reduced significantly (> 10%) for remanufacturing percentages of 55% and above. Research limitations/implications: There is a high degree of uncertainty associated with any forecast concerning post-vehicle-application lithium-ion batteries due to a lack of experience with their remanufacturing, repurposing, and recycling. Practical implications: Electrification of vehicles appears to be the only technically feasible approach to meeting government regulations concerning mileage and emissions (Center for Climate and Energy Solutions 2013). The planning in the present for the remanufacturing, repurposing, and recycling of the lithium-ion batteries used in electrification of vehicles is necessary. Capacity estimation is one important component of such planning. Social implications: The electrification of vehicles versus the use of fossil fuels is consistent with the guiding principles of sustainability in helping to meet current needs without compromising the needs and resources of future generations. Reusing entire lithium-ion batteries or recycling the materials of which they are composed further reinforces the sustainability of vehicle electrification. Originality/value: Estimates of recycling capacity needed in 2030, about 2.69M kWh, change little with the percent of post-vehicle-application batteries that are remanufactured. The need for significant recycling capacity appears between 2022 and 2024, increasing steadily thereafter. Similarly, the sum of remanufacturing and repurposing capacity is relatively constant indicating the need for flexible facilities that can do either task. In addition by 2030, up to approximately 25% of new battery production could be replaced by remanufactured batteries.
Keywords: 650; lithium-ion batteries; recycling; remanufacturing; repurposing; forecasting; mathematical modeling; simulation